The Effects of a Combined Alpha- and Beta-Blocking Drug, Labetalol, on Some Aspects of Platelet Function - Lote, Knut; Svenson, Birgit J; Ånstad, Unni; Nordøy, Arne (Thrombosis and Haemostasis, 1978)
The effects of the combined alpha- and beta-adrenoreceptor blocking agent labetalol on human blood platelets as estimated by platelet aggregation, platelet count, bleeding time and platelet factor 3 activity were studied in 5 patients. The drug reduced adrenaline - induced platelet aggregation in vitro. However, it did not influence the above platelet function test in therapeutic plasma concentrations in vivo.